The Distributional Justice of Oil Industry Social Development Projects and Oil Field Production Activities. Issue 2 (April 2020) - Fry, Matthew; Hilburn, Andrew
Highlights: Communities with high levels of oil production activities should also receive the most social development investments. Spatially fixed oil infrastructure serve as proxies for both risks and benefits in oil production areas. We found spatial overlap in social development interventions and oil extraction infrastructure at the regional scale. However, at the community scale, social development infrastructure and oil production activities are not evenly distributed. Premature investments, party politics, corruption, community capacity, and access to state support explain some of the unequal distributions. Abstract: In order to share the benefits of oil production with people living in extraction areas, the oil industry targets social development investments and projects to communities most affected by production activities. Yet, the effectiveness of industry-led community development projects remains unclear and under explored. In this study, we use a benefit-sharing, distributional justice framework to assess the efficacy of social development projects among 11 municipal governments and 114 local communities in the Tampico-Misantla Basin, a major oil extraction region in Mexico. To test for distributional justice, we use geospatial, rapid rural appraisal, and government data to compare the spatial overlap of oil production, pipelines, recent drilling activity, well counts, state-funded public works, and social marginalization indexes to social development infrastructure (e.g. paved roads, schools, bridges). We explain the uneven distribution of risks and benefits among some rural communities as the result of premature investments in social development projects, party politics, corruption, community capacity, and proximity to urban areas. This study contributes an empirical approach to evaluate distributional justice in oil extraction areas. It also provides insights into Mexico's oil sector during a period of significant neoliberal restructuring, most recently with the 2014 Energy Reforms.